Association between smoking status and non-alcoholic fatty liver disease - Hyun Joe; Jung-Eun Oh; Yong-Jin Cho; Hwang-Sik Shin (PLoS ONE, 2025)
Background The relationship between cigarette smoking and nonalcoholic fatty liver disease (NAFLD) remains controversial. Recent studies have demonstrated that cigarette smoking is a significant risk factor for the development of NAFLD. This study aimed to examine the association between smoking and NAFLD according to smoking status among Korean males, and to examine the relationship between smoking cessation and NAFLD. Methods This cross-sectional study included data from 12,241 adult males who underwent health checkups at a university hospital health promotion center between January 2018 and December 2019. Fatty liver was diagnosed using abdominal ultrasonography. The participants were categorized according to self-reported smoking status, pack-years, and period of smoking cessation. Odds ratio (OR) and corresponding 95% confidence interval (CI) for NAFLD were calculated using logistic regression analysis. Results After adjusting for confounding factors, the OR for NAFLD was 1.190 (95% CI 1.071–1.322, P = .001) among ex-smokers. Among current smokers, the risk for NAFLD increased with an increase in the amount of cigarette smoking (10–20 and ≥20 pack-years versus [vs.] never smoker, adjusted OR [aOR] 1.289 [95% CI 1.107–1.500]; P = .001 and 1.235 [95% CI 1.043–1.461]). The prevalence of NAFLD was inversely associated with the duration of smoking cessation (< 10 years vs. 10–20 years and ≥ 20 years; aOR 0.748 [95% CI 0.638–0.876], P < .001 and 0.750 [95% CI 0.592–0.950], P = .017, respectively). Conclusion Cigarette smoking was significantly associated with increased odds of NAFLD, whereas smoking cessation for more than 10 years was associated with decreased odds.